Transgender Health Advances and New Perspectives - Miguel Rios-González, Carlos (IntechOpen, 2022)
Trans people suffer from significant health disparities in multiple areas, one of which is ​​public health. Real or perceived stigma and discrimination within biomedicine and healthcare delivery, in general, can affect trans people's desire and ability to access appropriate care, thereby impacting their own health. The biggest barrier to both safe hormone therapy and adequate general medical care for transgender patients is the lack of access to care. Despite guidelines and data supporting the current transgender medicine treatment paradigm, trans patients report that a lack of providers experienced in trans medicine represents the single largest component inhibiting access. Transgender care is not taught in conventional medical training programs and very few doctors have the necessary knowledge and level of comfort. As such, this book provides up-to-date information on the health of transgender people. Chapters address such topics as standards for transgender care, the treatment of gender dysphoria, the lived experiences of transgender persons in Brazil and India, and much more.